Critical Appraisal of Emergency Medicine Education Research: The Best Publications of 2012. (March 2014) - Lin, Michelle; Fisher, Jonathan; Coates, Wendy C.; Farrell, Susan E.; Shayne, Philip; Maggio, Lauren; Kuhn, Gloria; DeIorio, Nicole M.
Abstract Objectives The objective was to critically appraise and highlight medical education research published in 2012 that was methodologically superior and whose outcomes were pertinent to teaching and education in emergency medicine (EM). Methods A search of the English language literature in 2012 querying Education Resources Information Center (ERIC), PsychInfo, PubMed, and Scopus identified EM studies using hypothesis‐testing or observational investigations of educational interventions. Two reviewers independently screened all of the publications and removed articles using established exclusion criteria. This year, publications limited to a single‐site survey design that measured satisfaction or self‐assessment on unvalidated instruments were not formally reviewed. Six reviewers then independently ranked all remaining publications using one of two scoring systems depending on whether the study methodology was primarily qualitative or quantitative. Each scoring system had nine criteria, including four related to methodology, that were chosen a priori, to standardize evaluation by reviewers. The quantitative study scoring system was used previously to appraise medical education published annually in 2008 through 2011, while a separate, new qualitative study scoring system was derived and implemented consisting of parallel metrics. Results Forty‐eight medical education research papers met the a priori criteria for inclusion, and 33 (30 quantitative and three qualitative studies) were reviewed. Seven quantitative and two qualitative studies met the criteria for inclusion as exemplary and are summarized in this article. Conclusions This critical appraisal series aims to promote superior education research by reviewing and highlighting nine of the 48 major education research studies with relevance to EM published in 2012. Current trends and common methodologic pitfalls in the 2012 papers are noted.